2012
DOI: 10.1002/jmv.23447
|View full text |Cite
|
Sign up to set email alerts
|

HIV gag‐specific immune response mediated by double negative (CD3+CD4CD8) T cells in HIV‐exposed seronegative individuals

Abstract: Double negative (DN) T cells are CD3(+), CD4(-), CD8(-) cells with either T-cell receptors (TCR) αβ or TCR γδ whose importance on protection against HIV infection is unknown. Since HIV-exposed seronegative individuals correspond to an ideal group in whom correlates of protection are expected, the role of these cells was studied in 13 HIV-serodiscordant couples in a stable relationship and reporting unprotected sexual intercourses. HIV-specific immune responses mediated by DN T-cells were evaluated by measuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…26 The same phenomena is well known in HIV-exposed individuals; T cells reactive to HIV present in some individuals exist in the absence of HIV-specific antibodies. [27][28][29][30][31][32][33][34] Similar observations are also made in Hepatitis Cand B-exposed individuals. [35][36][37][38] It is not known why serology tests for some viruses including HCMV are negative in some virus-exposed individuals.…”
Section: E982391-4 Volume 4 Issue 2 Oncoimmunologysupporting
confidence: 55%
“…26 The same phenomena is well known in HIV-exposed individuals; T cells reactive to HIV present in some individuals exist in the absence of HIV-specific antibodies. [27][28][29][30][31][32][33][34] Similar observations are also made in Hepatitis Cand B-exposed individuals. [35][36][37][38] It is not known why serology tests for some viruses including HCMV are negative in some virus-exposed individuals.…”
Section: E982391-4 Volume 4 Issue 2 Oncoimmunologysupporting
confidence: 55%
“…A de novo heterozygous mutation c.1192_1196delAGCCC (chr14: 99641977-99641981, NM_138576.2) was identified in BCL11B of the patient, resulting in a frameshift mutation p.S398Qfs * 117 that could produce truncated proteins (Figures 2B,C). The messy tail of the mutant protein was (7,(9)(10)(11).…”
Section: Sequencing Resultsmentioning
confidence: 99%
“…Bridgett Ryan-Payseur [ 24 ] demonstrated, in non-human primates, multi-effector-functional Vγ9Vδ2 T-cell responses against L. monocytogenes producing or coproducing Th1 and Th2 or Th17 cytokines, and direct lysis of L. monocytogenes-infected target cells. Restrepo et al [ 25 ] showed a higher expression of bi-functional γδ T-cell subsets coproducing IFNγ and MIP-1β in HIV-exposed seronegative individuals than in HIV-infected partners and healthy donors. However, our data could not be compared with these data, because these authors stimulated γδ T cells with HIV peptides and not with constitutive phosphoantigens.…”
Section: Discussionmentioning
confidence: 99%